Implementasi Framework CodeIgniter pada Pengembangan Sistem Layanan Akademik Terintegrasi di Politeknik Negeri Sriwijaya - Arif Prambayun; Muhammad Miftakul Amin; Teguh Noptriansyah; Muhammad Husain Gahara; Jurni Pradi Mulya Shakti (BETRIK, 2026)
The digitalization of academic services has become an urgent necessity for higher education institutions to enhance efficiency, transparency, and user satisfaction. Politeknik Negeri Sriwijaya still faces challenges in managing academic services such as warning letters, stop-out requests, and active study certificates, which are currently handled manually. This study aims to implement the CodeIgniter framework in developing an integrated web-based academic service system that can improve process efficiency and reduce administrative errors. The research employs the Software Development Life Cycle (SDLC) using the Waterfall model, consisting of the stages of requirements analysis, system design, implementation, testing, and evaluation. The developed system includes three main academic service modules, supported by a MySQL database and a Model-View-Controller (MVC) architecture. Functional testing results show that all features operate according to user requirements with a functional test pass rate of 98.6%              . Therefore, the implementation of CodeIgniter is proven effective in producing a structured, easily manageable, and adaptive system that meets the needs of vocational higher education institutions